2012
DOI: 10.29333/ojcmt/2373
|View full text |Cite
|
Sign up to set email alerts
|

Social Media: Changing Advertising Education

Abstract: Creating an academic assignment that closely parallels an advertising agency"s real world business experience is a challenge, but social media has destroyed many of the barriers that historically limited media options and completion of advertising plans. Because digital media is cost effective and easily used, commercials, videos, podcasts, and multimedia messaging can be filmed, edited, and broadcast, within the time frame of an advertising course This article presents an applied advertising project that inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Consistent with this perspective, situated learning theory is based on learning by doing through experiencing "hands-on, self-directed activities" in authentic settings (Wenger, 2009, p. 217). A related learning theory that is frequently studied in advertising and public relations research (Bush, 2009;Bush & Miller, 2011;Lester, 2012;Zwarun, 2007) is experiential learning, which scholars warn "is often misunderstood as a set of tools and techniques to provide learners with experiences from which they can learn" (Kolb & Kolb, 2005, p. 193). Instead, they suggested that experiential learning involves concrete experiences, observations and reflection rather than just a "mindless recording of experience" (Kolb & Kolb, 2005, p. 193).…”
Section: Learning Theoriesmentioning
confidence: 99%
“…Consistent with this perspective, situated learning theory is based on learning by doing through experiencing "hands-on, self-directed activities" in authentic settings (Wenger, 2009, p. 217). A related learning theory that is frequently studied in advertising and public relations research (Bush, 2009;Bush & Miller, 2011;Lester, 2012;Zwarun, 2007) is experiential learning, which scholars warn "is often misunderstood as a set of tools and techniques to provide learners with experiences from which they can learn" (Kolb & Kolb, 2005, p. 193). Instead, they suggested that experiential learning involves concrete experiences, observations and reflection rather than just a "mindless recording of experience" (Kolb & Kolb, 2005, p. 193).…”
Section: Learning Theoriesmentioning
confidence: 99%
“…İnternetin gelişmesi pek çok iletişim aracının kullanılmasına olanak sağlamıştır (Lester, 2012). www'nin açılımı World Wide Web olup "Geniş Dünya Ağı" anlamına gelmektedir.…”
Section: İnsan Kaynakları Kurumsal İletişim Web Siteleriunclassified
“…have various social media platforms where they market products and goods available on their websites. Lester (2012),states that "Social media venues are used for posting digitally produced items, driving traffic to the site, soliciting customer response, and generally creating a buzz thorough out the market" (p. 117). For Nigerian weddings, the key players involved in the process such as photographers, decorators, masters of ceremony, food vendors etc.…”
Section: Literature Review a Review Of Social Media And Advertisingmentioning
confidence: 99%